Preparing organisations for employee-driven open innovation - Oscar Amundsen; Tone Merethe Berg Aasen; Leif Jarle Gressgård; Kåre Hansen (International Journal of Business Science & Applied Management (IJBSAM), 2014)
The present study addresses the need to prepare organisations, small or large, for open innovation approaches, including the development of capacity to exploit the potential benefits of such principles through Employee-Driven Innovation (EDI). Based on interviews in 20 Norwegian enterprises, we propose that EDI is an under-explored opportunity in many organisations, and that the systematic introduction of EDI practices increases organisations' ability to exploit open innovation principles and favourably impacts the capacity for innovation. Specifically, EDI results in a more general interest in improvement among employees, increased engagement in innovation processes, and reduced opposition to change.
Keywords: 650; open innovation; employee-driven innovation; management; involvement; role performance; organisational culture; cultural characteristics; change